O-(Î²-hydroxyethyl)rutosides determination by micellar flow injection (FI)-spectrofluorimetry - Cecilia Mariana Peralta; Liliana Patricia FernÃ¡ndez (Elsevier, 2014)
A simple, eco-friendly, sensitive and economic flow injection spectrofluorimetric method was developed for the determination of O-(Î²-hydroxyethyl)rutosides. The procedure was based on the use of an anionic surfactant such as sodium dodecyl sulfate to provide an appreciable O-(Î²-hydroxyethyl)rutosides fluorescence enhancement, increasing considerably the sensitivity of detection. All the variables affecting the fluorescence intensity were studied and optimized. The flow rate was 5Â mL/min with detection at 450Â nm (after excitation at 346Â nm). A linear correlation between drug amount and peak area was established for O-(Î²-hydroxyethyl)rutosides in the range of 0.01â200Â Âµg/mL with a detection limit of 0.001Â Âµg/mL (s/n=3). Validation processes were performed by recovering studies with satisfactory results. The new methodology can be employed for the routine analysis of O-(Î²-hydroxyethyl)rutosides in bulks as well as in commercial formulations. Keywords: O-(Î²-hydroxyethyl)rutosides, Micellar enhancement, Flow injection, Spectrofluorimetry, Pharmaceuticals